2019
DOI: 10.1002/14651858.cd012845.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, vitamin D or recombinant parathyroid hormone for managing post-thyroidectomy hypoparathyroidism

Abstract: Calcium, vitamin D or recombinant parathyroid hormone for managing post-thyroidectomy hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 67 publications
2
29
1
1
Order By: Relevance
“…A study of 278 subjects found a percent of 27.3% positive for hypocalcemia and 15.1% for hypoparathyroidism (21). Based on this trial, the hypocalcemia differs with age, sex (females seems to have a higher risk), it is more frequent if lymph node dissection is associated to thyroid remove, it differs with type of thyroidectomy (as expected, larger dissections have a higher risk; also the intervention for recurrent goiter and second intervention for post-operatory bleeding increase the risk of hypocalcemia) and the duration of procedure and also if the PTH is low or lownormal pre-operatory the post-operative hypocalcemia is more frequent (21,22).…”
Section: General Datamentioning
confidence: 91%
See 3 more Smart Citations
“…A study of 278 subjects found a percent of 27.3% positive for hypocalcemia and 15.1% for hypoparathyroidism (21). Based on this trial, the hypocalcemia differs with age, sex (females seems to have a higher risk), it is more frequent if lymph node dissection is associated to thyroid remove, it differs with type of thyroidectomy (as expected, larger dissections have a higher risk; also the intervention for recurrent goiter and second intervention for post-operatory bleeding increase the risk of hypocalcemia) and the duration of procedure and also if the PTH is low or lownormal pre-operatory the post-operative hypocalcemia is more frequent (21,22).…”
Section: General Datamentioning
confidence: 91%
“…The most common risk factors of hypocalcemia after thyroidectomy have been widely analyzed (21,22). A study of 278 subjects found a percent of 27.3% positive for hypocalcemia and 15.1% for hypoparathyroidism (21).…”
Section: General Datamentioning
confidence: 99%
See 2 more Smart Citations
“…None of our patients developed hypercalcemia as a complication of supplemental treatment, 28 nor hematoma, permanent recurrent laryngeal nerve injury, or hypoparathyroidism as a complication of TT. 2,4,22,29e33 Vitamin D deficiency is considered a potential risk factor of postoperative hypoparathyroidism, and preoperative vitamin D supplementary treatment is preferable.…”
Section: Discussionmentioning
confidence: 63%